The short-term deterrent effect of executions: an analysis of daily homicide counts - Hong, Moonki (Crime & delinquency, 2018)
Does capital punishment exert any deterrent effect on homicide, above and beyond the effects of noncapital punishment? We hypothesized that potential deterrent effects should be strongest within a few days of executions because that was when news coverage peaked. We examined data on newspaper and national television news coverage, and found that it was largely confined to the period within a few days of executions. We analyzed state homicide counts for individual days from 1979 through 1998 (n = 372,555 state-days), following the methods of Grogger and controlling for size of the prison population. We found no significant homicide drops corresponding to temporal patterns of news coverage, with one exception: a small but significant drop on the days executions occurred.